Plan de negocios para la creación de un spa en la ciudad de Quevedo, periodo 2012 - Rojas Aguilera, Walter David. (2012)
Quevedo few years ago was considered a quiet town, where you could breathe fresh air and peace of its people was evident today with the advancement of science, technology and the growth of the city can be seen that no longer enjoy the peace of old, which brings the emergence of disease is stress millennium. For these reasons, in order to undertake this study was important to make a description of each of the services that will be offered, which will determine the dissatisfaction of the population, competitive analysis, marketing service that will differentiate ourselves , to implement is essential to have the necessary skilled workforce and that will provide a professional and personalized service, to finally undertake the remaining stages of the investment project, which will help determine the required investment, funding sources , production capacity, feasibility, balance point, and the results and the money will be handled every month during the first year of operation, in order to establish how the project will be profitable. Within this context set out to answer the following research question: Is it feasible to structure a business plan, which began with the market research that creates opportunities for the creation of a SPA, which contribute to the investment in such companies the city of Quevedo in the period 2012. The general objective was raised for this research was: To determine the feasibility of creating a spa in the city of Quevedo, through studies to help reduce uncertainty about investing in this company, period 2013., Deriving their main specific objectives : conducting market research, analyzing the demand for the service offered by the SPA, could Perform technical study that determined the size, distribution and location of the company and the process flow and determine the financial study project, developing budgets to determine the costs, investments and financing. It should be noted that the research was based on a descriptive and applied research aimed at studying, analyzing, describing and if necessary change the reality of the present nature of the problem under study. Further research will support the use of techniques such as interviews and survey where information is sought and provided directly to draw conclusions from the Market research indicates that there is sufficient demand, to implement the project SPA which will generate adequate annual profits, for this reason it is considered possible opening and analyzing from a technical and financial feasibility of the proposal by the estimated revenues as they have all the tools needed to implement the project as VAN financial indices: 294,271.71 TIR: 133.23% shows that are quantities that justify the development and viability of the same.